Diversity and function of soybean rhizosphere microbiome under nature farming - Agyekum, Dominic V. A.; Kobayashi, Tatsuyuki; Dastogeer, Khondoker M. G.; Yasuda, Michiko; Sarkodee-Addo, Elsie; Ratu, Safirah T. N.; Xu, Qicong; Miki, Takaaki; Matsuura, Eri; Okazaki, Shin (Frontiers in Microbiology, 2023)
Nature farming is a farming system that entails cultivating crops without using chemical fertilizers and pesticides. The present study investigated the bacterial and fungal communities in the rhizosphere of soybean grown in conventional and nature farming soils using wild-type and non-nodulating mutant soybean. The effect of soil fumigant was also analyzed to reveal its perturbation of microbial communities and subsequent effects on the growth of soybean. Overall, the wild-type soybean exhibited a better growth index compared to mutant soybean and especially in nature farming. Nodulation and arbuscular mycorrhiza (AM) fungi colonization were higher in plants under nature farming than in conventionally managed soil; however, fumigation drastically affected these symbioses with greater impacts on plants in nature farming soil. The rhizosphere microbiome diversity in nature farming was higher than that in conventional farming for both cultivars. However, the diversity was significantly decreased after fumigation treatment with a greater impact on nature farming. Principal coordinate analysis revealed that nature farming and conventional farming soil harbored distinct microbial communities and that soil fumigation significantly altered the communities in nature farming soils but not in conventional farming soils. Intriguingly, some beneficial microbial taxa related to plant growth and health, including Rhizobium, Streptomyces, Burkholderia, were found as distinct microbes in the nature farming soil but were selectively bleached by fumigant treatment. Network analysis revealed a highly complex microbial network with high taxa connectivity observed under nature farming soil than in conventional soil; however, fumigation strongly broke it. Overall, the results highlighted that nature farming embraced higher microbial diversity and the abundance of beneficial soil microbes with a complex and interconnected network structure, and also demonstrated the underlying resilience of the microbial community to environmental perturbations, which is critical under nature farming where chemical fertilizers and pesticides are not applied.